Wear performance of in-situ aluminum matrix composite after micro-arc oxidation - Erarslan, Yaman (ELSEVIER SCIENCE BV, 2013)
An attempt was made to modify the surface of in-situ aluminium matrix composite (AMC) by micro-arc oxidation (MAO). In the microstructure of AMC, CuAl2 reinforcements were generated by introducing 15% CuO into the aluminium melt. AMC was hot forged, homogenised, quenched and artificially aged before the MAO in a KOH, KF and Na2SiO3-containing electrolyte. After the MAO process the surface of the AMC was covered with Al2O3 coating having an effective thickness of about 15 mu m. Appearance of crack and/or delamination free zones at the periphery of the indent after the Rockwell C adhesion test indicated good adhesion between the composite and the Al2O3 coating. During dry sliding wear tests, this adherent Al(2)O(3)coating resisted the destructive action of the Al2O3 ball and provided about 15 times enhancement in wear resistance as compared to the original state.
Keywords: in situ composite; aluminum matrix composite; microarc oxidation; wear; tribology; PLASMA ELECTROLYTIC OXIDATION; REINFORCED ALUMINUM; CERAMIC COATINGS; PARTICLE-COMPOSITES; FABRICATION; BEHAVIOR; TRANSITIONS; MECHANISMS; TI-6AL-4V; FRICTION; Metallurgy & Metallurgical Engineering